A bibliometric analysis: Role of Artificial Intelligence on Accounting - Harahap, Cicely Delfina; Aryati, Titik (Ekonomi Digital, 2025)
Regarding artificial intelligence, this article aims to review previous research conducted by leading researchers on artificial intelligence, with a focus on the field of accounting through bibliometric analysis. Furthermore, this study will examine the impact of artificial intelligence on key topics, including auditing, accounting, taxation, and finance, in recent years through literature research. The analysis is conducted using the Scopus database and VOSviewer software, applying VOS mapping and clustering techniques to determine the scientific structure (countries, documents, institutions, keywords), visualize author networks, and identify research trends. The findings of this study will provide a systematic overview of the significant growth in the number of publications on AI. This research is expected to serve as a reference for the development of systematic literature reviews to identify, assess, and interpret all findings on the topic of artificial intelligence in accounting, thus allowing the literature review process to avoid bias and subjective interpretations by researchers